Impact of Social Media on Academic Performance of Graduate Students in Kathmandu - Hamal, Janga Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2021)
This study aims to identify the relationship of social media use on academic performance of students. The study is based on 176 sample responses generated from masters’ level second semester management students of different universities in Kathmandu. The study used structured questionnaires which constituted multiple choice and Likert scale items for collection of cross sectional data. The study has used descriptive analysis, frequency responses, and Chi-square test in order to identify significant differences in frequency of responses over different Likert scales and association between the variables. The study showed that engagement in social media has a negative relationship on academic performance of students. However, most students feel that its use should not be stopped. The study thus recommends that students need to be informed about pros and cons of social media, and the universities should engage students in teaching learning activities through social media.